EYA1 mutations leads to Branchio-Oto syndrome in two Chinese Han deaf families. (August 2019) - Chen, Penghui; Liu, Haijin; Lin, Yun; Xu, Jun; Zhu, Weidong; Wu, Hao; Yang, Tao
Abstract: Objectives: Branchio-Oto (BO) syndrome is one of the common syndromic forms of hearing loss. In this study, we aimed to characterize the clinical and genetic features of BO syndrome in two Chinese Han deaf families. Methods: The auditory and other BO-related clinical features of Family 1809 and Family 1974 were summarized. Targeted next-generation sequencing in 144 known deafness genes was performed in the probands. Co-segregation of the pathogenic mutations and the phenotype was confirmed by Sanger sequencing in the family members. Results: Interfamilial and intrafamilial variations can be observed in the clinical phenotypes of BO syndrome in Family 1809 and 1974. A novel c.1493_1494insAT (p.Ile498PhefsTer*3) mutation and a previous reported c.967-2A>G mutation in EYA1 were identified as the pathogenic cause in Family 1974 and 1809, respectively. Conclusion: Our results supported the heterogeneity of the genetic and phenotypic spectrum of BO syndrome. The recurrent c.967-2A>G in different ethnical groups suggested that it is a hot-spot mutation.